When does hearing laughter draw attention to happy faces? Task relevance determines the influence of a crossmodal affective context on emotional attention - Van Dessel, Pieter; Vogt, Julia (Frontiers in Human Neuroscience, 2012)
Prior evidence has shown that a person’s affective context influences attention to emotional stimuli. The present study investigated whether a crossmodal affective context that is induced by remembering an emotional sound modulates attention to visual emotional stimuli. One group of participants had to remember a positive, negative, or neutral sound during each trial of a dot probe paradigm. A second group of participants also had to encode the valence of the sound. The results revealed that attention was preferentially deployed to stimuli that were emotionally congruent to the affective context. However, this effect was only evident when participants had to encode the valence of the affective context. These findings suggest that a crossmodal affective context modulates the deployment of attention to emotional stimuli provided that the affective connotation of the context is task-relevant.